Interpersonal Caring Theory: An Empirical Test of Its Effectiveness Utilizing Growth Curve Analysis - II - Susie Kim, APRN, DNSc, FAAN; Sue Kim, RN, PhD, NP (Elsevier, 2007)
To test the impact of interpersonal caring theory empirically on six major psychosocial functioning outcomes of persons with serious mental illness. Methods: This was a quasi-experimental pre- and post-test design with data collection from a total of 266 patients with long-term serious mental illness, who were diagnosed with schizophrenia spectrum disorder and followed at 6-month intervals over a 24-month period in three groups: a community psychiatric service group, a community service with interpersonal caring intervention group, and a control group. Three hypotheses between the intensity, specificity, and longitudinality of services were tested using growth curve analysis. Results: Hierarchical linear modeling supported associations of hypotheses between the intensity, specificity, and longitudinality of services and improved patient outcomes. Conclusion: This study suggests that the intensity, specificity, and longitudinality of interpersonal caring interventions in community psychiatric service programs deserve attention in order to improve and maintain patient functional outcomes.